Enhancing educational and career prospects: A comprehensive analysis of institutional support for students with specific learning disabilities - Eseadi, Chiedu (International Journal of Research in Counseling and Education, 2023)
This study employs an integrative review methodology to investigate institutional support mechanisms for students with specific learning disabilities (SLDs), aiming to enhance their educational and career prospects. Extensive analysis of primary sources from databases including Dimension, ERIC, Scopus, Scilit, PubMed, Reference Citation Analysis, Google Scholar, and ResearchGate reveals critical insights. The research reveals that students with SLDs benefit from a spectrum of institutional support measures. These encompass provisions such as extended time allocations, access to study aids, dedicated personnel, financial assistance, and faith-based support. These interventions contribute not only to improved academic performance but also facilitate smoother transitions into the professional sphere. This study emphasizes the pressing need for institutions to fortify their support services dedicated to students with SLDs. It advocates for broader access to such resources, with the ultimate goal of optimizing the academic development and career prospects of this demographic. This approach serves to promote inclusivity and diversity in both educational and occupational domains.